Extracellular vesicles as biomarkers for traumatic brain injury using a 3D in vitro human brain tissue model - Peter Hsi; Vishal Tandon; David L. Kaplan (Scientific Reports)
Abstract Traumatic brain injury (TBI) is a significant health challenge worldwide, with current diagnostics and treatment falling short due to the complex pathophysiology involved. Extracellular vesicles (EVs) play a crucial role in brain injury response and are promising biomarkers for understanding the progression of TBI. A 3D in vitro human brain tissue model, comprising neurons, astrocytes, and microglia was utilized to simulate TBI and investigate EV responses. EVs were isolated at multiple acute timepoints post-injury and microRNA (miRNA) profiling revealed transient dysregulation of several miRNAs that aligned with clinical and in vivo studies. Pathway analysis revealed that these miRNAs are associated with the phosphoinositide 3-kinase / protein kinase B (PI3K / AKT) cell signaling pathway, a key regulator of neuroprotection, cell survival and injury response in TBI. The data suggest that temporal dysregulation of miRNAs plays a critical role in driving cellular responses following tissue injury and may serve as an initial snapshot of signaling following TBI, informing future investigations into long-term injury progression. Additionally, these findings demonstrate the utility of using an in vitro brain tissue model to study EVs in TBI to help identify potential biomarkers for clinical utility.